Investigating Types of Maxims Flouted in “Enola Holmes” Movie - Putri Melania; Mhd. Johan (LPPM Universitas Bumigora Mataram, 2022)
This research was done with the aim of investigating the flouting maxims types in characters’ utterances. The movie with the title “Enola Holmes” was taken as the data source for this research. The utterances that showed the flouting maxims phenomena were used as the data to be analyzed by researchers. In conducting this research, the researchers took the theory of Grice (1975) to analyze the flouting maxims utterances. Besides, the data were collected through the use of the observational method and non-participatory technique. The collected data then were analyzed by using the pragmatic identity method and pragmatic competence- in equalizing technique. The results discovered there were 16 data of flouting maxims in the movie. 1 data of flouting maxim of manner, 3 data of flouting maxim of quantity, 9 data of flouting maxim of relation, and 3 data of flouting maxim of quality were found in characters’ utterances. The most dominant maxim flouted in the utterances was flouting maxim of relation. It is because when communicating, the characters of the Enola Holmes movie respond irrelevantly to the topic being discussed.